Winter Bird Diversity and Abundance in Small Farmlands in a Megacity of Southern China - Lee, Myung-Bok; Chen, Daojian; Zou, Fasheng (Frontiers in Ecology and Evolution, 2022)
Urban expansion often accompanies a loss of natural habitats and arable lands but an increase in urban population. In China, vegetable-dominant small farmlands are common in urban/peri-urban areas. Some farmlands are also associated with government policy that aims to enhance local farmers’ livelihoods as well as increase food availability for city citizens. While small urban farmlands create open greenery cover that may provide birds with resources such as food and shelter, little attention has been given to understanding bird diversity in urban farmlands. Using two hierarchical models (multi-species occupancy model and N-mixture model), we examined how species richness and abundance of birds were associated with environmental characteristics within and surrounding urban farmlands in Guangzhou, one of the largest cities in China. We conducted crop and bird surveys at urban farmlands during two winter seasons between December 2019 and January 2021. Species richness increased with nonwoody (herbaceous ) vegetation cover within a farmland. Abundance of three species was also positively associated with the local nonwoody vegetation variable. Two species were more abundant at farmlands with higher crop diversity. Compositional features of matrix surrounding a farmland (a 500-m circular area) did not affect species richness. However, species richness and abundance of one species tended to decrease with increasing farmland fragmentation (patch density of farmlands) within a 1-km circular area. These findings suggest that 1) birds could be more influenced by environment features within farmlands than matrix features surrounding farmlands, 2) local uncultivated herbaceous vegetation is an important environmental feature, and 3) diverse crops in farmlands may benefit some birds. They also indicate that landscape pattern of farmlands, such as degree of fragmentation, could affect bird diversity in urban farmlands.